Key issues in North-western Mediterranean dry grassland restoration - Buisson, Elise; de Almeida, Tania; Durbecq, Aure; Arruda, André; Vidaller, Christel; Alignan, Jean‐françois; Toma, Tiago Shizen P.; Hess, Manon C.M.; Pavon, Daniel; Isselin‐nondedeu, Francis; Jaunatre, Renaud; Moinardeau, Cannelle; et al. (Restoration ecology, 2021)
Dry grasslands of the North‐western Mediterranean Basin are semi‐natural species‐rich ecosystems, composed of many annual species and some structuring perennial species. As these grasslands have been used as rangelands for centuries, human management (grazing; fire regimes) is one of their main ecological and evolutionary drivers, along with the Mediterranean climate. Despite EU conservation policy, damage to such grasslands still occurs and efficient ecological restoration is needed. This paper reviews restoration constraints, effective techniques, and research perspectives for restoring them in the light of their ecological characteristics. Major restoration constraints specifically include i) a poor contribution of the internal (seed bank) and external (seed rain) species pools, and ii) low establishment. The latter may be the result of the low seed quantity or quality of perennial species, stochastic or extended droughts, high soil nutrient content that may lead to competition (e.g. between weed and target species), inappropriate grazing management or fire regimes leading to shrub encroachment, or the death of target species seedlings in early stages of restoration. Successful restoration techniques include seeding, transplanting, hay transfer and timely soil transfer, all of which have to be adapted to regional plant phenology and to local Mediterranean climate. They must be combined with appropriate grazing or fire management. Their success may depend on years with particular rainfall amounts or patterns or on particular target plant species. We discuss research perspectives contributing to a better understanding of seed dispersal, seedling recruitment and soil processes and suggesting the benefits of using ecosystem engineer species.